Expert system for assessing the status of the access control system to the information environment of smart factory - Zaritskyi, O. (Проблеми керування та інформатики, 2025)
It is considered the topical issues of access control systems risk assessment of a single information environment of the smart production management system in connection with the risks that arise as a result of using the Internet of things (IoT) as an integral part of the Industry 4.0 concept. The author considered the properties of the IoT architecture from the point of view of its information security when integrated with a production management system. У статті розглянуто актуальні питання щодо оцінювання стану системи контролю доступу до єдиного інформаційного середовища системи керування розумним виробництвом у зв’язку з ризиками, що виникають унаслідок використання Інтернету речей як невід’ємної частини концепції Індустрії 4.0. Досліджено властивості архітектури Інтернету речей з погляду його інформаційної безпеки при інтеграції з системою керування виробництвом.